1966
DOI: 10.1037/h0023357
|View full text |Cite
|
Sign up to set email alerts
|

Effect of punishment duration and intensity on the extinction of an instrumental response.

Abstract: 2 factorial experiments were carried out in which a learned barriercrossing response by rats was punished with shocks of various durations and intensities during extinction. Each response during extinction was punished in Experiment I until a criterion of extinction was attained; only the 1st response during extinction was punished in Experiment II. In general, the degree of depression in response strength produced by punishment was directly related to its intensity and to its duration. Amount of postpunishmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

1970
1970
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…Another type of data lends support to the hypothesis that the activity D and the Now Print signal N both exist but respond to the US in different ways. These data show that an increase in US duration can significantly increase the strength of emotional conditioning (Ashton, Bitgood, and Moore, 1969;Boe, 1966;Borozci, Storms, and Broen, 1964;Church, Raymond, and Beauchamp, 1967;Keehn, 1963;Strouthes, 1965). How can a brief Now Print signal N whose duration does not increase significantly with US duration coexist with emotional conditioning properties that do increase significantly with US duration?…”
Section: The Asymmetry Between Cs and Us Processing In Timing Controlmentioning
confidence: 99%
“…Another type of data lends support to the hypothesis that the activity D and the Now Print signal N both exist but respond to the US in different ways. These data show that an increase in US duration can significantly increase the strength of emotional conditioning (Ashton, Bitgood, and Moore, 1969;Boe, 1966;Borozci, Storms, and Broen, 1964;Church, Raymond, and Beauchamp, 1967;Keehn, 1963;Strouthes, 1965). How can a brief Now Print signal N whose duration does not increase significantly with US duration coexist with emotional conditioning properties that do increase significantly with US duration?…”
Section: The Asymmetry Between Cs and Us Processing In Timing Controlmentioning
confidence: 99%
“…Second, although the shock schedule may have seemed dense, it was relatively lean when compared with previous research. In fact, in early studies on punishment, it was common to deliver shock on an FR‐1 schedule (Azrin, 1959, 1960; Azrin & Holz, 1961; Boe, 1966; Boroczi et al, 1964; Holz et al, 1963; Karsh, 1962; Seligman & Campbell, 1965). In the present study, usually less than 50% of responses were followed by shock, except when 0.8‐mA shock was used.…”
Section: Discussionmentioning
confidence: 99%
“…This paradoxical effect has been observed with a variety of subjects (e.g., monkeys, rats, and pigeons), operants (e.g., lever presses and key pecks), and reinforcers (e.g., monkey chow, pellets, and access to grain). Whether shock increases or decreases response rates may depend on several factors including the schedule of shock, the schedule of reinforcement, the manner of introducing shock, shock duration, shock frequency, shock intensity, and the interresponse times (IRTs) followed by shock (Arbuckle & Lattal, 1992; Azrin & Holz, 1966; Baron, 1991; Boe, 1966; Church, 1963; Sizemore & Maxwell, 1985). Of present interest are two of these factors: shock intensity and the IRTs followed by shock.…”
mentioning
confidence: 99%
“…Church, Raymond, & Beauchamp (1967) reported that shock duration and intensity combine to determine the severity of punishment. It was therefore hypothesized that bar-trained rats, when punished at different intensities and durations of shock, would require different numbers of presses to reach a nonresponse criterion.…”
mentioning
confidence: 99%
“…It was therefore hypothesized that bar-trained rats, when punished at different intensities and durations of shock, would require different numbers of presses to reach a nonresponse criterion. Boe (1966) found that the amount of recovery from punishment depends on the degree of punishment-induced suppression in response Bull. Psychon.…”
mentioning
confidence: 99%